Analysing and experimenting the preparation of Gelatin Methacryloyl for 3D bioprinting - Alen, Niina (My University, 2022)
The process of preparing Gelatin Methacryloyl (GelMA) is analysed and tested. The thesis begins with an overview of 3D bioprinting, optimal properties of materials used in 3D bioprinting, and an introduction of GelMA. The steps of preparing GelMA are then analysed based on literature and new ways of analysing the protocol are discussed. The preparation of GelMA consists of the synthesis, filtering, freeze-drying, and the measurement of the degree of substitution. The synthesis is examined for technique and transparency. Two methods of filtering GelMA are then being analysed and tested. Dialysis is a widely used method of filtering GelMA but its duration lacks standardization. A method of determining when the dialysis is ready is being developed. Another filtering method, preparative cromatography, is tested. Chromatography is tested because it could be a faster filtering method compared to dialysis. The theory of freeze-drying is analysed next and the method is tested in action in the experimental section. Lastly, the method of measuring the degree of substitution is being analysed and tested. As a result, all of the steps in the process of preparing GelMA are examined and an optimal method for the process is suggested. The analysis of preparing GelMA raised discussion and new ideas for further development and research.
Keywords: Gelatin Methacryloyl, quality control, synthesis, dialysis, freeze-drying, degree of substitution